Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Intern Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Badung - Ida Ayu Widiastuti; Sang Ayu Putu Arie Indraswarawati; I Made Endra Lesmana Putra (UNHI Press, 2023)
Human resource expertise, internal control mechanisms, and IT usage all helped improve Badung Regency's financial reporting. This research examines if Human Resources Expertise, Internal Control Mechanisms, and IT affect Badung Regency's consolidated financial statements. This study examines how Badung Regency's HR, Internal Control Mechanisms, and IT affect government finances. Based on a survey of 182 OPD financial staff in Badung Regency. 72 representative samples were chosen using